A simple simulator to teach enzyme kinetics dynamics. Application in a problem-solving exercise. Issue 1 (1st January 2017) - Torres, Néstor; Santos, Guido
Abstract: Enzyme kinetics is an essential part of biochemistry programs, which have been gaining importance in recent years for their applications in biotechnology and biomedicine. The teaching and learning of these issues has been traditionally hampered by difficulties that stem mainly from the dynamic and mathematical nature of the topic and the introduction of some abstract concepts. In this paper, we propose a simple, home-made application developed in Excel or, alternatively, in Libre Office (SIMENKIN), which allows students to view and interact with the dynamics of enzymatic reactions. The contribution of this specific application stems from the simulation of substrate loss and the associated initial rate of the enzyme catalysed reaction over time, which is not always incorporated into these packages. We illustrate its use applying it in a practical problem-solving approach module, designed to facilitate the learning of the fundamental concepts of enzyme kinetics.